A community based study on haemoglobinopathies and G6PD deficiency among particularly vulnerable tribal groups in hard-to-reach malaria endemic areas of Odisha, India: implications on malaria control - Sujata Dixit; Arundhuti Das; Ramakanta Rana; Hemant K. Khuntia; Akhil B. Ota; Sanghamitra Pati; Madhusmita Bal; Manoranjan Ranjit (Malaria Journal, 2022)
Abstract Background Haemoglobinopathies and G6PD deficiency are inherited disorders found mostly in malaria-endemic areas among different tribal groups of India. However, epidemiological data specific to Particularly Vulnerable Tribal Groups (PVTGs), important for planning and implementing malaria programmes, is limited. Therefore, the present community-based study aimed to assess the prevalence of haemoglobinopathies and G6PD deficiency among the 13 PVTGs found in the state of Odisha, reporting the maximum malaria cases in the country. Methods This cross-sectional study was conducted from July 2018 to February 2019 in 12 districts, home to all 13 PVTGs, in an estimated sample size of 1461, selected two-stage sampling method. Detection of haemoglobinopathies was done by the variant analyser. Screening of G6PD deficiency was carried out using DPIP method followed by quantification using spectrophotometry. The PCR–RFLP technology was used to determine variant of G6PD deficiency and haplotype analysis of sickle cell, while ARMS-PCR and GAP-PCR was used for detecting the mutation pattern in β-thalassaemia and α-thalassaemia respectively. The diagnosis of malaria was done by Pf-PAN RDT as point of care, followed by nPCR for confirmation and Plasmodium species identification. Results The prevalence of sickle cell heterozygotes (AS) was 3.4%, sickle cell homozygous (SS) 0.1%, β-thalassaemia heterozygotes 0.3%, HbS/β-thalassaemia compound heterozygote 0.07%, HbS-α-thalassaemia 2.1%, G6PD deficiency 3.2% and malaria 8.1%. Molecular characterization of βS revealed the presence of Arab-Indian haplotype in all HbS cases and IVS 1–5 G → C mutation in all β-thalassaemia cases. In case of α-thal, αα/α-3.7 gene deletion was most frequent (38%), followed by αα/α-4.2 (18%) and α-3.7/α-3.7 (4%). The frequency of G6PD Orissa (131C → G) mutation was found to be 97.9% and G6PD Mediterranean (563C → T) 2.1%. Around 57.4% of G6PD deficient individuals and 16% of the AS were found to be malaria positive. Conclusion The present study reveals wide spread prevalence of sickle cell anaemia, α-thalassaemia, G6PD deficiency and malaria in the studied population. Moderate to high prevalence of G6PD deficiency and malaria warrants G6PD testing before treating with primaquine (PQ) for radical cure of Plasmodium vivax. Screening and counselling for HbS is required for the PVTGs of Odisha.